A Mass Spectrometric Assay of METTL3/METTL14 Methyltransferase Activity. (April 2020) - Buker, Shane M.; Gurard-Levin, Zachary A.; Wheeler, Benjamin D.; Scholle, Michael D.; Case, April W.; Hirsch, Jeffrey L.; Ribich, Scott; Copeland, Robert A.; Boriack-Sjodin, P. Ann
A variety of covalent modifications of RNA have been identified and demonstrated to affect RNA processing, stability, and translation. Methylation of adenosine at the N6 position (m 6 A) in messenger RNA (mRNA) is currently the most well-studied RNA modification and is catalyzed by the RNA methyltransferase complex METTL3/METTL14. Once generated, m 6 A can modulate mRNA splicing, export, localization, degradation, and translation. Although potent and selective inhibitors exist for several members of the Type I S -adenosylmethionine (SAM)-dependent methyltransferase family, no inhibitors have been reported for METTL3/METTL14 to date. To facilitate drug discovery efforts, a sensitive and robust mass spectrometry–based assay for METTL3/METTL14 using self-assembled monolayer desorption/ionization (SAMDI) technology has been developed. The assay uses an 11-nucleotide single-stranded RNA compared to a previously reported 27-nucleotide substrate. IC50 values of mechanism-based inhibitors S -adenosylhomocysteine (SAH) and sinefungin (SFG) are comparable between the SAMDI and radiometric assays that use the same substrate. This work demonstrates that SAMDI technology is amenable to RNA substrates and can be used for high-throughput screening and compound characterization for RNA-modifying enzymes.